1996
DOI: 10.1002/(sici)1097-0142(19960901)78:5<1089::aid-cncr20>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life after cystectomy or conservative therapy for patients with infiltrating bladder carcinoma: A survey by a self‐administered questionnaire

Abstract: QOL is better after conservative therapy than after cystectomy, as expected. Prospective studies with repeated measurements covering all fields of interest in QOL would offer an accurate assessment of QOL in NMBC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 0 publications
2
24
0
1
Order By: Relevance
“…The self-assessment by patients is in agreement with the investigators' evaluation. At the time of the study, a specific module for urinary symptoms of the QLQC-30 questionnaire was not available, and a specific questionnaire was built, based on other published studies (17,18). Using this tool, 70% of patients maintained a good score for bladder function 12 months after treatment.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The self-assessment by patients is in agreement with the investigators' evaluation. At the time of the study, a specific module for urinary symptoms of the QLQC-30 questionnaire was not available, and a specific questionnaire was built, based on other published studies (17,18). Using this tool, 70% of patients maintained a good score for bladder function 12 months after treatment.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, after surgery only 13% had had intercourse, and none had ejaculated. Caffo et al (18) carried out a retrospective study by mailing a questionnaire to 93 patients treated with radiation with or without chemotherapy or by cystectomy. The QoL after surgery was reduced by lack of sexual activity and a worsened physical condition.…”
Section: Discussionmentioning
confidence: 99%
“…This can be assessed more adequately by quality-of-life questionnaires. When patients who underwent radical cystectomy were compared with patients treated by chemoradiation, Caffo et al [24] found that the quality of life after cystectomy was lowered by the presence of stoma, decreased sexual activity, and worsened physical condition. In another study, it was found that patients who had an orthotopic reconstruction had better quality of life than patients who had an ileal conduit did [25].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] Only three studies have used validated quality-of-life surveys to evaluate patients. [11][12][13] Other studies have improperly compared nonrandomized groups of patients with continent diversions with those with conduits.…”
mentioning
confidence: 99%